Measuring the Effectiveness of Social Protection Concepts and Applications - Yemtsov, Ruslan (The World Bank, 2017)
'Measuring the Effectiveness of Social Protection: Concepts and Applications' provides the conceptual and analytical framework for assessing social protection (SP) programs, as well as provides a practical guide for users seeking to conduct analysis, particularly using the World Bank's Software Platform for Automated Economic Analysis (ADePT). The manual provides a comprehensive unique resource to tie together social policy theory, concepts and practical analytical techniques.The book content is targeted at policymakers and practitioners worldwide seeking to improve the outcomes of their social protection policies. It suggests advanced methods and a new rapid analysis instrumental for technical experts working on quantitative SP analysis for their ministry, national statistics offices, think tanks, universities, or development organizations.The book aims to equip users with different statistical background and SP knowledge to independently conduct SP analysis and prepare a standardized set of tables and graphs to conduct different types of SP performance analysis, ranging from benchmarking SP performance within and across countries, simulating the performance of alternative reform options, and assessing the viability of proposed programs